Concepciones de los estudiantes sobre una magnitud "olvidada" en la enseñanza de la química: la cantidad de sustancia - Furió-Mas, Carles; Azcona, Rafael; Guisasola, G.; Mujika, E. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1993)
The main objective of this paper is the identification of the students' representations about the idea of substance quantity and to see to what extent the establised Chemistry teaching in Secondary schools contributes to giving them a more atomist view of matter. The results obtained in this work confirm that students, upon completing their studies, have practically not changed their `globalise conception of substance quantity, and only half of those that studied chemistry master the necessary activity to be able to understand the mole concept.